Analysis of Constraints Affecting Beneficiaries under Pradhan Mantri Krishi Sinchayee Yojana in Odisha - Tripathy, Maitreyee; Mishra, Bishnupriya; Satapathy, Guru Prasad; Das, Sarbani (Indian Journal of Extension Education, 2023)
The study was conducted in 2021 in the Jharsuguda district of Odisha to identify the constraints affecting beneficiaries under the Pradhan Mantri Krishi Sinchayee Yojana (PMKSY). The study used a random sampling procedure and collected data through personal interviews with 60 respondents. Garrett’s ranking technique was employed to analyze the constraints as perceived by farmers. The findings revealed that medium and large landholding farmers availed the maximum limit of subsidy, and non-availability of spare parts in the local area, tedious procedures to obtain the benefit of PMKSY, and frequent equipment repairs were the major challenges hindering the performance of beneficiaries under PMKSY. Therefore, key stakeholders must take suitable steps to remove the identified constraints. It is imperative to address these challenges to improve the performance of farmers in Odisha.
Keywords: PMKSY; Garrett’s ranking; Farmers; Constraints